2023
DOI: 10.48138/cjo.1210594
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Health Perception and Life Satisfaction of Elderly People Living in Nursing Homes

Abstract: This research was conducted to examine the relationship between health perception and life satisfaction of elderly people living in nursing homes. This study, which was conducted in accordance with the descriptive research principles seeking relationship, was conducted with elderly individuals living in five nursing homes in Samsun between March and July 2019. Sample selection was not made within the scope of the research, and 129 elderly individuals aged 65 and over were reached. The data of the study were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The average life satisfaction scale score of the elderly people included in the study was calculated as 26.22 ± 5.37. In a study conducted in another city in Turkey using the same scale, the life satisfaction score of the elderly living in a nursing home was determined as 14.4±4.81 [ 23 ].This study demonstrated the significant convergent validity of the Turkish NHAS with the Life Satisfaction Scale. This means that residents who are well-adjusted to the nursing home are likely to have high life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The average life satisfaction scale score of the elderly people included in the study was calculated as 26.22 ± 5.37. In a study conducted in another city in Turkey using the same scale, the life satisfaction score of the elderly living in a nursing home was determined as 14.4±4.81 [ 23 ].This study demonstrated the significant convergent validity of the Turkish NHAS with the Life Satisfaction Scale. This means that residents who are well-adjusted to the nursing home are likely to have high life satisfaction.…”
Section: Discussionmentioning
confidence: 99%